ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA ARITMATIKA SOSIAL BERDASARKAN NEWMAN ERROR ANALYSIS - Rita M Luhukay; Wilmintjie Mataheru; Juliana S Molle (Science Map Journal, 2023)
This study aims to find out the mistakes made by class VII students of SMP Negeri 3 Ambon in solving social arithmetic story problems based on Newman Error Analysis (NEA), with the type of qualitative research. Sources of data, namely class VII SMP Negeri 3 Ambon and subject teachers. Subjects were taken by giving tests to 21 students, then 3 students were selected as subjects based on the most errors made by students. The 3 subjects, namely IT, AD, and TM. Data collection techniques include tests, interviews and video recordings. Data analysis techniques include data reduction, data presentation and data verification. The results showed that IT subjects made reading errors and encoding errors, AD subjects made reading errors, transformation errors and encoding errors, and TM subjects made all errors, namely reading errors, comprehension errors, transformation errors, process skills errors and encoding errors